Hypertrophic Obstructive Cardiomyopathy Masked by Tako-Tsubo Syndrome: A Case Report - Y. Daralammori; M. El Garhy; M. R. Gayed; A. Farah; B. Lauer; M. A. Secknus (Case Reports in Cardiology)
Introduction. Left ventricular outflow obstruction might be part of the pathophysiological mechanism of Tako-tsubo cardiomyopathy. This obstruction can be masked by Tako-tsubo cardiomyopathy and diagnosed only by followup. Case Presentation. A 70-year-old female presented with Tako-tsubo cardiomyopathy and masked obstructive hypertrophic cardiomyopathy at presentation. Conclusion. Tako-tsubo cardiomyopathy typically presents like an acute MI and is characterized by severe, but transient, regional left ventricular systolic dysfunction. Prompt evaluation of the coronary status is, therefore, mandatory. The prognosis under medical treatment of heart failure symptoms and watchful waiting is favourable. Previous studies showed that LVOT obstruction might be part of the pathophysiological mechanism of TCM. This paper supports this theory. However, TCM may also mask any preexisting LVOT obstruction.